(untitled) (Research, Society and Development, 2022)
This article aims to verify the impacts of the occupational therapist’s interventions through group body practices with a clientele affected by neck pain. This is a qualitative, descriptive and intervention-type research. The theoretical framework was elaborated from the context of neck pain and occupational therapy, focusing on the body and its occupational dimensions. A semi-structured interview, body practices and a field diary were used for data collection. The sample consisted of six (6) participants with a diagnosis of neck pain, enrolled in the Teaching and Assistance Unit in Physiotherapy and Occupational Therapy (UEAFTO). Data analysis was performed using the content analysis technique. The results obtained showed that there were adequate coping strategies to alleviate stress and neck pain, as well as promoting the learning of psychosocial skills, with transformations, producing new bodies, with their meanings and their reconstructions in their daily activities, favoring self-perception, self-motivation and consequently a better occupational performance. In this way, the research verified the effectiveness of the occupational therapist’s intervention with this clientele.